Kaempferol Inhibits the Primary Attachment Phase of Biofilm Formation in Staphylococcus aureus - Ming, Di; Wang, Dacheng; Cao, Fengjiao; Xiang, Hua; Mu, Dan; Cao, Junjie; Li, Bangbang; Zhong, Ling; Dong, Xiaoyun; Zhong, Xiaobo; Wang, Lin; Wang, Tiedong (Frontiers in Microbiology, 2017)
The ability to form biofilms on surfaces makes Staphylococcus aureus the main pathogenic factor in implanted medical device infections. The aim of this study was to discover a biofilm inhibitor distinct from the antibiotics used to prevent infections resulting from S. aureus biofilms. Here, we describe kaempferol, a small molecule with anti-biofilm activity that specifically inhibited the formation of S. aureus biofilms. Crystal violet (CV) staining and fluorescence microscopy clearly showed that 64 μg/ml kaempferol inhibited biofilm formation by 80%. Meanwhile, the minimum inhibitory concentration (MIC) and growth curve results indicated that kaempferol had no antibacterial activity against the tested bacterial strain. Kaempferol inhibited the primary attachment phase of biofilm formation, as determined by a fibrinogen-binding assay. Moreover, a fluorescence resonance energy transfer (FRET) assay and quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR) analyses revealed that kaempferol reduced the activity of S. aureus sortaseA (SrtA) and the expression of adhesion-related genes. Based on these results, kaempferol provides a starting point for the development of novel anti-biofilm drugs, which may decrease the risk of bacterial drug resistance, to prevent S. aureus biofilm-related infections.